2023
DOI: 10.3390/molecules28093880
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound–Microwave Combined Extraction of Novel Polysaccharide Fractions from Lycium barbarum Leaves and Their In Vitro Hypoglycemic and Antioxidant Activities

Abstract: Ultrasound–microwave combined extraction (UMCE), gradient ethanol precipitation, chemical characterization, and antioxidant and hypoglycemic activities of Lycium barbarum leaf polysaccharides (LLP) were systematically studied. The optimal conditions for UMCE of LLP achieved by response surface method (RSM) were as follows: microwave time of 16 min, ultrasonic time of 20 min, particle size of 100 mesh, and ratio of liquid to solid of 55:1. Three novel polysaccharide fractions (LLP30, LLP50, LLP70) with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…During this process, the enzymes break down the plant cell wall into small molecules, then intracellular L. japonica polysaccharides are rapidly released in the external medium. However, a combination of multiple methods is preferred to a single extraction method [ 33 , 34 ]. The Ultrasonic-assisted enzymatic extraction (UAEE) method is a combination of ultrasonic extraction technology and enzymatic hydrolysis, and has a high extraction rate, short extraction time, low extraction temperature, and high efficiency [ 35 , 36 ].…”
Section: Extraction and Purification Methods Of L Japonica ...mentioning
confidence: 99%
“…During this process, the enzymes break down the plant cell wall into small molecules, then intracellular L. japonica polysaccharides are rapidly released in the external medium. However, a combination of multiple methods is preferred to a single extraction method [ 33 , 34 ]. The Ultrasonic-assisted enzymatic extraction (UAEE) method is a combination of ultrasonic extraction technology and enzymatic hydrolysis, and has a high extraction rate, short extraction time, low extraction temperature, and high efficiency [ 35 , 36 ].…”
Section: Extraction and Purification Methods Of L Japonica ...mentioning
confidence: 99%
“…The results showed that the optimal conditions of LBP extraction using combined methods were 16 min for microwave extraction, 20 min for ultrasound extraction, and liquid-solid ratio of 55:1. Under these optimized conditions, the polysaccharide yield was 1.873% [22].…”
Section: Active Ingredients 21 Lycium Barbarum Polysaccharidementioning
confidence: 97%
“…It has been identified that the polysaccharides from Lycium barbarum leaves hinder α-amylase enzyme activity in a dose-dependent manner [ 149 ]. Another polysaccharide (SGP-1-1), isolated from Siraitia grosvenorii, showed α-amylase inhibition with the best inhibition of 61.73% [ 148 ].…”
Section: Secondary Metabolites Isolated From Various Plant Sources As...mentioning
confidence: 99%